Islamic Education in Addressing Ethical and Moral Challenges Faced by Students in the Digital Era - Salma Nabilah Hidayat; Syamsul Aripin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has brought significant changes in student behavior patterns, particularly in how they interact and communicate in the digital space. However, this progress has not been fully accompanied by ethical and moral maturity, giving rise to various problems such as the use of impolite language, the spread of unverified information, and aggressive behavior on social media. This phenomenon of low digital ethics among students poses a serious challenge to the world of education. This study aims to analyze the role of Islamic education in fostering digital ethics among students in the digital era. The method used is a literature study with a qualitative approach through a review of various relevant scientific sources, such as journal articles, books, and academic publications related to Islamic education and digital ethics. The results of the study indicate that Islamic education plays a crucial role in shaping students' digital ethics by reinforcing Islamic values such as etiquette, morality, trustworthiness, honesty, and tabayyun (religious observance). The integration of these values into the learning process, along with the role models of Islamic Religious Education teachers, contributes to building students' moral awareness, enabling them to use digital technology wisely, responsibly, and with dignity.